Network design and performance analysis of geographical routing protocol in mobile Ad-Hoc networks - Alam, Abu Hasnat Md. Riadul; Khan, Md. Atiqur Rahaman; Uddin, Jia (© 2013 IEEE, 2016)
This conference paper was presented in the 2013 2nd International Conference on Informatics, Electronics and Vision, ICIEV 2013; Dhaka; Bangladesh; 17 May 2013 through 18 May 2013. [© 2013 IEEE] The conference paper's definite version is available at: :http://dx.doi.org/10.1109/ICIEV.2013.6572533